1998
DOI: 10.1007/bf01682168
|View full text |Cite
|
Sign up to set email alerts
|

Detection of human herpesviruses 6 and 7 in heart transplant recipients by a multiplex polymerase chain reaction method

Abstract: In order to evaluate the possible reactivation of human herpesviruses 6 (HHV-6) and 7 (HHV-7) after heart transplantation, buffy-coat and plasma specimens from 21 transplant patients and 56 healthy blood donors were examined for HHV-6 and HHV-7 DNA by polymerase chain reaction. Human herpesvirus 6 and HHV-7 infection or reactivation has been suggested to play a role in cytomegalovirus disease progression in renal transplant recipients. In the present study, however, no significant difference in the prevalence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…The controversy about the influence between HHV‐6 and HHV‐7 replication and CMV infection is not resolved [8, 9]. In this study, we could observed that CMV replication was longer in the presence of HHV‐6 viremia: 40 ± 25 days versus 18 ± 16 days ( P = 0.0001).…”
Section: Incidence Apparition and Duration Of CMV Hhv‐6 And Hhv‐7 Vmentioning
confidence: 56%
“…The controversy about the influence between HHV‐6 and HHV‐7 replication and CMV infection is not resolved [8, 9]. In this study, we could observed that CMV replication was longer in the presence of HHV‐6 viremia: 40 ± 25 days versus 18 ± 16 days ( P = 0.0001).…”
Section: Incidence Apparition and Duration Of CMV Hhv‐6 And Hhv‐7 Vmentioning
confidence: 56%
“…It is also important to screen adult recipients for antibodies to EBV, since seronegative recipients of organs from infected donors are at increased risk for the development of post-transplant lymphoproliferative disorder [42]. Screening of donor or recipient for human herpesvirus-6 (HHV-6) or HHV-8 is not routinely performed; the impact of HHV-6 infection in heart transplant patients has not yet been clearly defined [43], and the rare occurrence of Kaposi's sarcoma among heart transplant recipients (less than 1%) [44] makes population screening impractical.…”
Section: Donor and Recipient Serologic Screeningmentioning
confidence: 99%
“…The development of a sensitive and rapid diagnostic assay is necessary for the early initiation of antiviral therapy to avoid complications and loss of the transplanted organ [1,2,5]. A prospective laboratory and clinical study that involved a subgroup of kidney transplant recipients was performed to assess a longitudinal analysis of the clinical impact of plasma herpesvirus viremia and CMV urine excretion in this population.…”
Section: Longitudinal Study Of Herpesviruses In Kidney Transplant Recmentioning
confidence: 99%